Escritas entrecruzadas: leitura das crônicas e contos de Rachel de Queiroz (1928-1952) - Silva, Regina Helena Ribeiro (2012)
This research focuses on the literary-journalistic activity of Rachel de Queiroz (1910-2003), published in Ceará and Rio de Janeiro press, within the period of 1928 to 1952, which it is shaped into a scenario where a mobile writing exercise plays a key role in her writing skills development. With the access to primary sources that are composed of files scanned from original texts, it becomes possible to analyze Rachel de Queiroz chronicle production in the context of her writing connected with the development of the Brazilian press throughout the first half of the twentieth century. This research is based on critics and theorists of literature as Antonio Candido, Massaud Moisés, Roland Barthes, Davi Arrigucci Jr., Haroldo de Campos, Henry James, Julio Cortázar, as well as historians Eric Hobsbawm, Durval Muniz Jr, Maria Helena Capelato, Nicolau Sevcenko and social historians of Communication such as Asa Briggs, Peter Burke, Cristiane Costa, Gerald Nobre, and theorists of Journalism highlighting Alceu Amoroso Lima, Nilson Lage and José Marques de Melo. Thus, the objectives of this research contains the analysis and interpretation of a set of texts in which it is possible to identify literary-journalistic elements that stand out among this crossing of written materials and take place in a field of constant boundaries shifts of literary and journalistic genres. Divided into three parts, this research presents in the first chapter, the historical development of the chronicle genre in Brazil as literary activity that marks the beginning of the writing of Rachel de Queiroz. In the second section, it is highlighted the reflection on the chronicle genre, which boundaries move between Literature and Journalism. Moreover, the research analyzes the elements that distinguish the writing of Rachel de Queiroz in the composition of the language with which the author builds the texts published in newspapers. The third chapter consists of the analysis and interpretation of an anthology of short stories from the writer selected among the group of 168 chronicles that composed the corpus of this research.